2016
DOI: 10.20286/hpr-010261
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Quality of Work Life of Medical Staff and Quality of Patient Care

Abstract: Background: Nowadays, quality of patient care is one of the major and important concerns of health care delivery which is extremely dependent on the medical staff. Objectives: The purpose of this study was to investigate the relationship between Quality of Work Life (QWL) and quality of patient care. Methods: This study was a descriptive-analytic study based on correlation which was conducted in the educational hospitals of Kermanshah. A total of 320 medical staffs were selected for the study. Quality of Work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…On well-being, the outcome of our research is in keeping with those of other researchers 44 , 45 who reported that good well-being at work will improve the quality of care rendered by HCPs. Findings from the present study are also consistent with previous studies which have reported a relationship between the well-being of HCPs and the quality and safety of patient’s care 46 49 .…”
Section: Discussionsupporting
confidence: 87%
“…On well-being, the outcome of our research is in keeping with those of other researchers 44 , 45 who reported that good well-being at work will improve the quality of care rendered by HCPs. Findings from the present study are also consistent with previous studies which have reported a relationship between the well-being of HCPs and the quality and safety of patient’s care 46 49 .…”
Section: Discussionsupporting
confidence: 87%
“…26 27 44-46 Also, either high-quality care leading to residents' favourable outcomes, or residents' functional performance itself being maintained or improved, might in turn promote the happiness of care staff through professional fulfilment. 47 The results here are not robust, possibly due to a limited number of observations for examining this correlation. In subgroup analyses on residents with each required care level, statistically significant differences were observed only in residents with a required care level may tend to be irreversibly disabled with static diseases.…”
Section: Discussionmentioning
confidence: 65%
“… 26 27 44–46 Also, either high-quality care leading to residents’ favourable outcomes, or residents’ functional performance itself being maintained or improved, might in turn promote the happiness of care staff through professional fulfilment. 47 …”
Section: Discussionmentioning
confidence: 99%
“…QWL not only effects staff performance but also predicts quality of organization service (Mohammed J Almalk, 2012). It was noted that QWL of physicians is higher than that of non-physicians (nurses and other front line health workers) (Mohammadi-Bolbanabad, 2016). QWL not only focuses on the work life but non-work life as well (Bruno Del Sarto Azevedo, 2017).…”
Section: Quality Of Work Lifementioning
confidence: 99%
“…Many Nurses were reluctant to perform their duties and were filing for resignations due to high level of work stress, anxiety and depression (Laura Lorente, 2020) (Ali Hasanpour Dehkordi, 2020). Studies show that the working environment and work load has had a major impact on personal health of the frontline workers which in turn increases the psychological distress among the working staff, leading to inefficiency to carry on their tasks (Mohammadi-Bolbanabad, 2016). Nurses during the early stages of covid 19 had faced a huge amount of psychological distress and anxiety not only because of high work load but also because of lack of proper medical equipment, and knowledge of the fast-spreading virus and direct contact with the patients (Zhang, 2020) (Catton, 2020).…”
Section: Introductionmentioning
confidence: 99%